2004
DOI: 10.3168/jds.s0022-0302(04)73521-3
|View full text |Cite
|
Sign up to set email alerts
|

Measures of Bone Mineral Content in Mature Dairy Cows

Abstract: The objectives of this investigation were to assess the relationship between chemical measures and imaging estimates (radiographic photometry and dual-energy x-ray absorptiometry) of bone mineral content in dairy cows and to evaluate the effects of parity, stage of lactation, and site of measurement (fused third and fourth metacarpal bone vs. caudal vertebrae 14 and 15) on bone mineral content. In a preliminary study, the caudal vertebrae were excised from 33 cows following slaughter. Samples were analyzed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…The results from the present study and the Moore et al (2000) and Kamiya et al (2005) studies taken together would suggest that although primiparous cows resorb more bone compared with multiparous cows, they also replace that bone throughout lactation. Keene et al (2004) measured bone mineral content (BMC) in cadaver Holstein metacarpal and caudal vertebrae to evaluate effects of parity. Total BMC concentration (ash, % of bone DM) was not affected by parity but Ca and P concentration of the metacarpal vertebrae increased with parity.…”
Section: Effect Of Paritymentioning
confidence: 99%
“…The results from the present study and the Moore et al (2000) and Kamiya et al (2005) studies taken together would suggest that although primiparous cows resorb more bone compared with multiparous cows, they also replace that bone throughout lactation. Keene et al (2004) measured bone mineral content (BMC) in cadaver Holstein metacarpal and caudal vertebrae to evaluate effects of parity. Total BMC concentration (ash, % of bone DM) was not affected by parity but Ca and P concentration of the metacarpal vertebrae increased with parity.…”
Section: Effect Of Paritymentioning
confidence: 99%
“…During the last decade, the dual‐energy X‐ray absorptiometry technique (DXA) has been considered ‘the gold standard’ to evaluate BMD in human beings (Fogelman and Blake, 2000). It has also been increasingly applied, among the various areas of large animal medicine, for both ex vivo and in vivo studies in pigs (Mitchell et al., 2001), sheep (Pouilles et al., 2000), horses (McClure et al., 2001; Carstanjen et al., 2003a, b), bovine calves (Scholz et al., 2003) and dairy cows (Keene et al., 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, variations in bone mineralization have been reported in relation to diet in dogs (Lauten et al., 2002), horses (Hoffman et al., 1999;Shea Porr et al., 2000) and beef cattle (Shupe et al., 1988; Williams et al., 1990; Beighle et al., 1995, 1997; Motsei and Beighle, 2006). Lastly, the stages of lactation and parity have been reported to affect BMD in both mares (Glade, 1993) and dairy cows (Beighle, 1999; Keene et al., 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Little (1972) described a method that surgically removes a small disc (biopsy) from the 11 th or 12 th rib, usually 20 cm from the spine. This method has consistently demonstrated significant differences between cattle fed different dietary P intakes, and so this has become the main method used for measuring P status (Little, 1972;Little and Shaw, 1979;Hoey et al, 1982;Read et al, 1986b;Ternouth, 1990;de Waal and Koekemoer, 1997;Keene et al, 2004). Units of measure have developed and changed over time.…”
Section: Bonementioning
confidence: 99%
“…However, this technology is still limited by the aforementioned limitations on rib CBT in that parts of the skeleton accrete and metabolise differently and correlations with whole skeletal phosphorus have not been identified. Keene et al (2004) stated that "non-invasive imaging techniques are not sufficiently sensitive to detect changes in mineral content or composition of mature cows, and only modest changes in bone mineral can be observed with stage of lactation and parity". Zotti et al (2010) suggested that the main limitation to absorptiometry technology is the lack of reference values for bone mineral density in cattle, as it is the "gold standard" for evaluating the bone mineral density in humans.…”
Section: Bonementioning
confidence: 99%